Experimental investigation of flow control devices effect on inclusion separation in a four strand tundish. (2nd October 2019) - Mosalman Yazdi, Mohamad Reza; Khorasani, Ahmad Reza Faghih; Talebi, Shahram
ABSTRACT: In continuous casting, molten steel often contains non-metallic inclusions that have a very high melting temperature and thus remain suspended in the molten flow. Given the lower density of these substances compared to the melt, they can be filtered in the form of top slag by proper use of buoyancy forces. Thus, providing a desirable flow pattern, reduced flow turbulence, and adequate residence time for inclusions in the tundish will improve the inclusion separation performance and therefore the product quality. In this study, a reduced-scale water model of a tundish was used to evaluate the effect of melt level in the tundish on the flow pattern and inclusion separation performance. Then, the flow control devices are added to this simple tundish model to examine the effect of them on the flow behaviour and inclusion separation. Experimental investigation showed that raising the water level in the model tundish has desirable effects on inclusion separation and the use of the dam at the inlet with tall dam improves the flow pattern and inclusion separation almost 20% in the form of top slag.